Ethical Attitudes of Accountants: Recent Evidence from a Practitioners’ Survey - Emerson, Tisha L. N.; Conroy, Stephen J.; Stanley, Charles W. (2007)
Recent highly publicized ethical breaches including those at Enron and WorldCom have focused attention on ethical behavior within the accounting profession. At the heart of the debate is whether ethical attitudes of accountants are to blame. Using a nationally representative sample of accounting practitioners and a multidisciplinary student sample at two Southern United States universities, we compare sample responses to 25 ethically charged vignettes to test whether they differ. Overall, we find no significant difference – even for a specific “accounting tricks” vignette, which resembles the Enron and WorldCom situations. We do find, however, that the practitioners were more accepting of vignettes that involved physical harm (PH) to individuals and those that were legal (but ethically questionable). We postulate that accounting practitioners may apply a legalistic framework to their assessment of the acceptability of each vignette. Focusing on an “accounting tricks” vignette, we also find no significant difference between auditors and institutional practitioners compared to all other types of accountants in the sample. We conclude that ethical attitudes of accounting practitioners do not differ significantly by specialty area.
Keywords: ethical attitudes; empirical analysis of business ethics; Enron; Business Ethics; accounting scandals; accounting practitioners; Accountants